The Future of Blockchain Consensus. - GRAMOLI, VINCENT; QIANG TANG (Communications of the ACM, 2023)
The article offers information on the Redbelly Blockchain. Blockchain consensus, performance, and protocols are discussed. According to the article, the Redbelly Blockchain was added to the Australian National Blockchain Roadmap. The Dumbo path, the asynchronous consensus, and the Bolt-Dumbo-Transformer are also mentioned.